1998
DOI: 10.1002/(sici)1097-0223(199810)18:10<1086::aid-pd393>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Schwangerschafts protein 1 (SP1) adds little to the age-related detection of fetal Down syndrome in the first trimester of pregnancy

Abstract: Schwangerschafts Protein 1 (SP1), being a placental protein appearing in the maternal circulation early in pregnancy, has been investigated as a potential marker for Down syndrome in the first trimester. Our study compared SP1 levels in 15 pregnancies with a Down syndrome fetus and 97 matched controls. Although the median MoM in Down syndrome pregnancies (0·49) was lower than in controls, its use as a marker added very little to the detection rate above the maternal age alone. Copyright © 1998 John Wiley & Son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These were 65 of the 77 cases and 318 of the 383 controls used in previous analyses of different serum markers (Wald et al, 1996) (those with serum samples still available) plus some more recent samples. None of the samples had been used in previous SP1 studies; we excluded five cases and their corresponding controls from Groningen, Netherlands, because they were the subject of a previous report (Kornman et al, 1998). The SP1 assays were performed at the Statum Serum Institut in Copenhagen, without knowledge of whether each sample came from a case or control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were 65 of the 77 cases and 318 of the 383 controls used in previous analyses of different serum markers (Wald et al, 1996) (those with serum samples still available) plus some more recent samples. None of the samples had been used in previous SP1 studies; we excluded five cases and their corresponding controls from Groningen, Netherlands, because they were the subject of a previous report (Kornman et al, 1998). The SP1 assays were performed at the Statum Serum Institut in Copenhagen, without knowledge of whether each sample came from a case or control.…”
Section: Methodsmentioning
confidence: 99%
“…During the first trimester of pregnancy (8 to 14 weeks' gestational age), the maternal serum concentration of pregnancy-specific beta-1-glycoprotein (otherwise known as Schwangerschafts protein 1, SP1) tends to be lower in pregnancies associated with Down syndrome than in unaffected pregnancies. While several previous studies have found lower values in Down syndrome pregnancies (Brizot et al, 1995;Brock et al, 1990;Kornman et al, 1998;Qin et al, 1997;Macintosh et al, 1993;Aitken et al, 1993;Brambati et al, 1991), the size of the association is uncertain: estimates have varied considerably between 0.27 multiples of the median (MOM) and 0.89 MOM. The variation may be partly explained by the small size of many of the studies.…”
Section: Introductionmentioning
confidence: 95%
“…Besides PAPP-A, more potential markers were studied (e.g. SP1 (Kornman et al, 1998) andCA125 (Van Lith et al, 1993)), but none of those turned out to be worth adding to the screening test. The search for DS screening markers was not limited to biochemical markers; an enlarged nuchal translucency (NT) on a first trimester ultrasound scan also turned out to be predictive for DS (Nicolaides et al, 1992, Pandya et al, 1994.…”
Section: Prenatal Screening For Down Syndromementioning
confidence: 99%